Quantum Mechanical Calculations and Electrochemical Study of Vibrational Frequencies, Energies in Some Flavonoids molecules - Razooqi, Mustafa S.; Al-Ani, Huda N. (Iraqi Journal of Science, 2022)
Quantum mechanical computations is conducted using DFT (Density Functional Theory) and PM3 (Parameterized Model 3), also, using DFT of (B3LYP) with a 6-311++G (d, p) with G09 application. These molecular three components include structure, electronic charge density and energetic characteristics of chosen phytomedicine compounds. The impact of functional groups on physical characteristics were studied using myricetin, linebacker, and flavone because of their chemical structures. For phytomedicine compounds, we utilized quantum mechanical simulations to estimate bond length, energy, vibration(vib.) modes, charge density and mechanical properties (cruelty, strength, stiffness, for the measurements of the lengths and energy of the bonds). Herzberg convention is used to look for the connections between the frequencies of similar modes which was used. IR absorption of the highest vibration frequencies modes of 3N-6 was measured and assigned for all species. Physical parameters were also calculated these include: heat of production, amount of energy, atomic electronic charge density, dipole moment and (E gap) (E = ELUMO-EHOMO). For three phytomedicine molecules, quantum chemical properties were combined. This software also computed and evaluated the electronic charge density distribution on atoms of 3 molecules. The equilibrium geometries of all three molecules were studied.